2019
DOI: 10.1021/acsami.8b22157
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide Film Characteristics for Cathodic Stripping Voltammetry

Abstract: The combination of conductivity, optical transparency, and wide anodic potential window has driven significant interest in indium tin oxide (ITO) as an electrode material for electrochemical measurements. More recently, ITO has been applied to the detection of trace metals using cathodic stripping voltammetry (CSV), specifically manganese (Mn). However, the optimization of ITO fabrication for a voltammetric method such as CSV is yet to be reported, nor have the microstructural properties of ITO been investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…It was also reported that ITO could also be utilized for sensing manganese (Mn) species by CSV. [116] In this case, the annealing process could increase the grain size and enhance the crystalline structure. After obtaining the stripping voltammograms, it was concluded that annealed ITO electrodes were an optimum option to determine Mn(II) with a detection limit of 0.1 ppb.…”
Section: Indium-based Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also reported that ITO could also be utilized for sensing manganese (Mn) species by CSV. [116] In this case, the annealing process could increase the grain size and enhance the crystalline structure. After obtaining the stripping voltammograms, it was concluded that annealed ITO electrodes were an optimum option to determine Mn(II) with a detection limit of 0.1 ppb.…”
Section: Indium-based Electrodesmentioning
confidence: 99%
“…ITO electrode modified with Au nanoparticles [114] Hg(II): 0.03 Water and soil samples Hg(II): 0.1-10 µg L −1 DPASV, pH: 2.0, E d and t d : 0.30 V for 300 s, E step : 4 mV ITO chip sensor modified with Au nanoparticles [115] Hg(II): 0.11 Lake water samples Hg(II): 0.63-80 ppb DPASV combined with online flow system, pH: 4.3, E d and t d : 0.60 V for 180 s, E step : 4 mV ITO on Si substrate electrode [116] Mn(II): 0.1 Chemical reagents Mn(II): 1-50 ppb CSV, pH: 5.0, E d and t d : 1.20 V for 180 s, E step : 4 mV ITO coated with polystyrene-blockpoly(ethylene-ran-butylene)-blockpolystyrene-sulfonate (SSEBS) [117] Mn(II): 0.060 Water samples Mn(II): 18-1800 nm CSV, pH: 5.0, E d and t d : 1.20 V for 180 s, E step : 5 mV…”
Section: Tin-based Electrodesmentioning
confidence: 99%
“…Especially for the utilization in bioelectronics and photoelectrocatalysis purposes, contact with an electrolytic environment demands the characterization of an inert electrochemical potential window . Since ITO is already in an oxidized form, the positive potential window is large . However, multiple cathodic reduction pathways at negative potential are possible depending on the electrolyte specifications, where reductive degradation is promoted under acidic conditions and rather inhibited in a basic environment. Acidic chemical degradation has been reported even at solid interfaces. , Typically, this leads to a visible darkening of the ITO layer caused by the reductive formation of metallic indium and tin nanoparticles and, finally, a loss of electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…17 Therefore, the ITO film exhibits a higher carrier density and a wider optical band gap (above 3.5 eV). 18 Doping of the foreign metal Ag into an ITO film can not only maintain the basic properties of the ITO film but also effectively tune the carrier density and improve some characteristics, such as electrical and optical characteristics. 19 Ag/ITO was cosputtered on a 2D ordered polystyrene (PS) template (a schematic of the preparation of the cosputtered Ag/ITO film is shown in Supporting Information (SI) Figure S1).…”
mentioning
confidence: 99%
“…The introduction of defects forms a shallow donor or impurity level near the conduction band and provides free electrons . Therefore, the ITO film exhibits a higher carrier density and a wider optical band gap (above 3.5 eV) . Doping of the foreign metal Ag into an ITO film can not only maintain the basic properties of the ITO film but also effectively tune the carrier density and improve some characteristics, such as electrical and optical characteristics …”
mentioning
confidence: 99%